“Measuring the factors affecting Job Characteristics with Personal outcomes” (A Case Study of Khairpur Sugar Mill) - Lashari, Aamir Ali; Shah, Imran Ahmed; Malkawy, Sahira; Parveen, Shahdma (Archives of Business Research, 2019)
The fundamental purpose behind this research was to find out the association amongst job characteristics and personal outcomes of the representatives of Khairpur sugar factory. The quantitative and qualitative methods have been used to analyze the data and interpret the results. In this research personal outcome, such as satisfaction, internal work motivation and growth were the dependent factors and independent variables were job characteristics like skill variety, task identity, task significance, autonomy, feedback, policy practices and benefits. The present studies led to the laborers of Khairpur sugar mill and total workers were 394 and only 78 workers were randomly selected for this study. Essential information gathered through sample received from the employment indicative overview survey (Hackman & Oldham, 1975) . The secondary sources incorporate journals, annual reports and unpublished research works. Statistical software for social science (SPSS version 21) and descriptive survey was used to analyze data and multiple regressions were applied to establish the correlation between independent and dependent variables. After analyzing the results, it is concluded that job characteristics such as skill variety shows the significant relationship with personal outcomes which is at the level of .000 as well as task identity, task significance and benefits have a positive relationship with personal outcomes such as (internal work motivation, satisfaction and growth) but autonomy, feedback and policy & practices shows less significant impact on personal outcomes.